LEGAL PROTECTION OF CHILDREN AS VICTIMS OF SEXUAL VIOLENCE IN PERSPECTIVE HUMAN RIGHTS: PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN KEKERASAN SEKSEUAL DALAM PERSPEKTIF HAK ASASI MANUSIA - Lestari Hulu, Insafkan (UPMI Proceeding Series, 2024)
Sexual violence against children is one of the acts that violate human rights. As is known that the 1945 Constitution of the Republic of Indonesia and the Law on Human Rights. Therefore, the protection of children from violence should be respected, upheld, and enhanced human dignity without discrimination, welfare and justice for children. Violence is any unlawful act with or without using means against the physical and psychological that causes danger to life, body, or causes the deprivation of a child's freedom. The purpose of this study is an effort to provide legal protection to children who are victims of sexuality from a human rights perspective. By using a normative legal research method based on primary, secondary and tertiary legal materials, such as laws and regulations, legal theory, and can be in the form of expert opinions related to existing problems. The results of this study were then analyzed qualitatively with descriptive-descriptive presentation. Then it was found that the existence of child victims of sexual violence had not received adequate services so that efforts were needed to protect legal protection for child victims of sexual violence with the aim of providing guarantees and protecting their rights so that they can live, grow, develop and participate optimally, and obtain protection from violence and discrimination.